The effect of N+ ion energy on the properties of ion bombarded plasma polymer films - Rangel, E. C.; da Cruz, N. C.; Tabacniks, M. H.; Lepienski, C. M. (Elsevier B.V., 2001)
This work describes the influence of the ion bombardment on the electrical, optical and mechanical properties of polymer films deposited from radio-frequency plasmas of benzene. Irradiations were conducted using N+ at 5 x 10(19) ions/m(2), varying the ion energy, E-0, from 0 to 150 keV. Film elemental composition was determined by Rutherford backscattering spectroscopy. Electrical resistivity and hardness were obtained by the two-point probe and nanoindentation technique, respectively. Ultraviolet-visible spectroscopy was employed to investigate the optical constants of the samples. Etching rate was determined by exposure of the films to reactive oxygen plasmas. Ion bombardment induced gradual loss of H and increase in C and O concentrations with Eo. As a consequence the electrical, optical and mechanical properties were drastically affected. Interpretation of these results is proposed in terms of chain cross-linking and unsaturation. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: ion implantation; plasma polymer; electrical resistivity; optical absorption; hardness